(untitled) (Conferencea, 2022)
Hemorrhagic stroke(HS) is a significant risk factor for post-stroke epilepsy. According to the literature, 8.4% of patients with hemorrhagic stroke experienced seizures within the first 24 hours from the onset of a stroke, compared with other types of strokes The aim of this study was to study the clinical features of the course of early epileptic seizures in patients with HS.